FRI0434 Patient and provider factors associated with compliance with rheumatoid arthritis treatment recommendations. (23rd January 2014) - Harrold, L.; Reed, G.; Saunders, K.; Shan, Y.; Spruill, T.; Greenberg, J.
Abstract : Background: Prior work has shown that only approximately 50% of rheumatoid arthritis (RA) patients in the US receive the recommended treatment in response to active disease. Therefore understanding the factors associated with recommended management is essential in order to improve RA care. Objectives: To identify the patient and provider characteristics associated with compliance with treatment recommendations published by the American College of Rheumatology (ACR) for the use of biologic and nonbiologic disease modifying anti-rheumatic drugs (DMARDs) in the management of RA using data from a multi-center observational registry within the United States (the Consortium of Rheumatology Researchers of North America: CORRONA) with >30, 000 RA patients. Methods: We identified biologic naïve RA patients cared for by US rheumatologists participating in the CORRONA registry between 12/08 and 12/11. Initiation or dose escalation of biologic and nonbiologic DMARDs in response to active disease (using the Clinical Disease Activity Index) was assessed in comparison to the ACR recommendations. The population was divided into two mutually exclusive cohorts: 1) methotrexate (MTX) only users; and 2) multiple non-biologic DMARD users. We compared the characteristics of patients (age, gender, race/ethnicity, working status, insurance and RA disease characteristics) who received care consistent with the ACR recommendations and their treating providers (academic vs. private practice and region of the country [Northeast, South, Midwest and West]) to those who did not in the two cohorts using logistic regression adjusting for clustering of physicians and patients. Results: There were 2, 200 patients who met inclusion criteria cared for by 180 providers at 86 practice sites. Of the 991 MTX only users with active disease (moderate disease activity with a poor prognosis or high disease activity), 44% received care consistent with the treatment recommendations. In adjusted analyses, female gender (OR 1.49; 95% CI 1.12-1.99), high disease activity (OR 1.49, 95% CI 1.14-1.93), and prior use of prednisone (OR 1.35, 95%CI 1.05-1.75) were all associated with receipt of the recommended care. Among the 1209 multiple nonbiologic DMARD users with moderate or high disease activity, 48% received care consistent with the recommendations. Prior use of prednisone (OR 1.27, 95% 1.00-1.59), residence in the Northeast (OR 1.56, 95% CI 1.15-2.11) and care by an academic rheumatologist (OR 1.63, 95% CI 1.13-2.35) in adjusted analyses was associated with recommended care while patient age ≥65 was associated with reduced compliance (OR 0.75, 95% CI 0.59-0.95). Conclusions: Compliance with the ACR treatment recommendations varied based on both patient and provider characteristics. Identification of these characteristics will help us identify which patients and providers to target for interventions to improve care. Disclosure of Interest: L. Harrold Consultant for: CORRONA, G. Reed Grant/Research support from: CORRONA, Consultant for: CORRONA, Employee of: University of Massachusetts Medical School, Paid Instructor for: Harvard Medical School, K. Saunders Employee of: CORRONA, Y. Shan Employee of: University of Massachusetts Medical School, T. Spruill Grant/Research support from: NIH/NHLBI K23HL086734, Employee of: NYU Longone Medical Center, J. Greenberg Shareholder of: CORRONA, Consultant for: AstraZeneca, Novartis, Pfizer, CORRONA